Construction of Ideal Remote Assessment Environments and the Impact of Self-Selected Music on Student Performance - Joshua K. C. Tsang; Kyle J. Wilby (University of Minnesota Libraries Publishing, 2021)
Background: Remote online assessments require students to construct their own assessment environments, including selection of strategies (such as the use of music) to reduce stress. This study aimed to determine the impact of self-selected music on student performance during a remote online assessment and to identify factors important for constructing ideal assessment environments. Methods: Final year students were randomized to complete a voluntary remote online 2-hour care plan test. Those randomized to 'music' were required to play self-selected music during the assessment and those randomized to 'non-music' were asked not to play music. Prior to the assessment, perceived stress and resilience were measured. Performance between groups was compared and associations between stress, resilience, and performance determined. A post-survey identified music preferences/acceptability, and factors identified for ideal remote assessment environments. Results: A total of 79 students completed the study (n=40 music, n=39 non-music). The median assessment score in the music group was 90% (range 58 to 99%) and 88% (range 58 to 99%) in the non-music group (not significant). No associations were found between scores and perceived stress or resilience. The majority of students randomized to music (62.5%) found it helpful. Thirteen categories of factors were identified to contribute to an ideal remote assessment environment with the most common being lighting, location, quietness, distractions, and seating/set-up. Conclusion: Findings support the notion that remote online assessment environments should not come as 'one size fits all' and many factors (including self-selected music) may influence a student's ability to perform to a high standard.